Women’s Solutions for Amazon Conservation and Sustainable Development - Center for International Forestry Research (Center for International Forestry Research, 2022)
The Women’s Solutions for Amazon Conservation and Sustainable Development study is an initiative by the Amazon Sustainable Landscapes Program (ASL) which seeks to develop a strategy